Juridical Review of Government Legal Measures for Ensuring Rights of Patients with Mental Disorders in Social Security Administration - Wuryani, Ayu Indah; Kaseger, Henny; Tamaka, Ryny Silvana; Tampil, Velecia Criselda; Issalillah, Fayola (Metromedia, 2023)
ABSTRACT – Mental health is still a significant health issue throughout the world, including in Indonesia. Most families in Indonesia still consider that having a family member with mental health problems is something to be ashamed of. In health law, special protection is provided by health service providers. For this reason, this study will explore the Juridical Review regarding the Government's Legal Policy in Providing Protection of the Rights of Social Security Administering Bodies for Health to Patients Suffering from Mental Disorders. The study method used is a normative juridical study with a conceptual approach and statutory analysis. The study results show the implementation of this policy still has shortcomings, which causes patient dissatisfaction with hospital services. One of the problems detected was the lack of information conveyed by health facilities to participants of the Health Social Security Administering Agency. Provisions for legal protection for individuals experiencing mental disorders are explained in Article 4 paragraph 1 letters c and d of Law Number 18 of 2018 concerning Mental Health, which discusses healing and rehabilitation health care initiatives.